2007
DOI: 10.1029/2005ja011475
|View full text |Cite
|
Sign up to set email alerts
|

Solar cycle signature and secular long‐term trend in OH airglow temperature observations at South Pole, Antarctica

Abstract: We have examined Michelson Interferometer OH airglow temperature data to investigate solar cycle and long‐term variations of mesospheric temperatures at South Pole Station (SPS), Antarctica (90°S). The data set used here is continuous (24 hours a day) and taken during 1994–2004 austral winters. We have used a Multiple Linear Regression (MLR) technique to elucidate solar cycle and the trend term in the MI temperature time series data. The 11‐year time series of OH rotational temperature shows a strong correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 43 publications
9
31
0
Order By: Relevance
“…The possible correlation of high-latitude OH temperatures with the solar flux is open to question as studies of OH temperatures at mid-to-high latitudes by Bittner et al (2002) found no such correlation, and an analysis by Sigernes et al (2003) of 20 years of data acquired at Svalbard, 781N also found no solar influence. However, in the Antarctic, Azeem et al (2007) did find a strong correlation of OH rotational temperatures with the solar flux. It will be of great interest to extend this apparent correlation in relation to the solar flux.…”
Section: Article In Pressmentioning
confidence: 82%
“…The possible correlation of high-latitude OH temperatures with the solar flux is open to question as studies of OH temperatures at mid-to-high latitudes by Bittner et al (2002) found no such correlation, and an analysis by Sigernes et al (2003) of 20 years of data acquired at Svalbard, 781N also found no solar influence. However, in the Antarctic, Azeem et al (2007) did find a strong correlation of OH rotational temperatures with the solar flux. It will be of great interest to extend this apparent correlation in relation to the solar flux.…”
Section: Article In Pressmentioning
confidence: 82%
“…Correlation between SSN and the OH* residuals may be biased by that even though the number of sunspots may be zero for many days in a row, the OH* temperatures still vary. The correlations are overall lower than correlations achieved for some other high‐latitude sites [ Azeem et al ., ; French and Klekociuk , ]. The correlation increases slightly when excluding SSW months, except for SSN.…”
Section: Resultsmentioning
confidence: 99%
“…The solar heating is dominated by the absorption of solar UV radiation by O 2 and O 3 [Mlynczak and Solomon, 1993]. Many studies in the past attempted to find out the contribution of solar heating on the mesopause temperatures Azeem et al, 2007]. These studies reported a strong linear relation between the mesopause temperature and the F10.7 cm radio flux using the nighttime hydroxyl measurements Azeem et al, 2007].…”
Section: Variability Of Daytime Mesopause Temperature During the Daymentioning
confidence: 99%
“…Many studies in the past attempted to find out the contribution of solar heating on the mesopause temperatures Azeem et al, 2007]. These studies reported a strong linear relation between the mesopause temperature and the F10.7 cm radio flux using the nighttime hydroxyl measurements Azeem et al, 2007]. In addition to the solar heating, a significant part of the mesospheric energetics is contributed by the exothermic reactions involving odd-oxygen and odd-hydrogen species, including quenching of excited photolysis products [Mlynczak and Solomon, 1993], by radiative cooling associated with infrared emission of CO 2 at 15 mm [Andrews et al, 1987;Rodgers et al, 1992].…”
Section: Variability Of Daytime Mesopause Temperature During the Daymentioning
confidence: 99%